2020
DOI: 10.3389/fonc.2020.00059
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Cell Therapy: A Novel and Potential Immunotherapy for Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is the most common primary brain tumor in adults with very poor prognosis and few advances in its treatment. Recently, fast-growing cancer immunotherapy provides a glimmer of hope for GBM treatment. Adoptive cell therapy (ACT) aims at infusing immune cells with direct anti-tumor activity, including tumor-infiltrating lymphocyte (TIL) transfer and genetically engineered T cells transfer. For example, complete regressions in patients with melanoma and refractory lymphoma have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 132 publications
(143 reference statements)
0
28
0
Order By: Relevance
“…The clinical trials, ClinicalTrials.gov NCT identifiers: NCT02208362, NCT01454596, NCT01109095, targeting IL-13Rα2, EGFRvIII, and HER2, respectively, provide useful insights on the immunotherapeutic ability of CAR T cells against gliomas (Migliorini et al, 2018). These trials showed the CAR T cells': low toxicity, moderate ability to traffic to the glioma microenvironment, limited ability to target glioma cells, and inconsistent results in increasing overall survival (Migliorini et al, 2018;Akhavan et al, 2019;Wang et al, 2020). For example, HER2-specific CAR T cells, in the NCT01109095 NCT00648739 Samalizumab Glioblastoma Recruiting Wright et al (2000), Gorczynski et al (2000), Wright et al (2003) trial, were used to treat 17 patients with progressive GBM (Ahmed et al, 2017).…”
Section: Car-t Cellsmentioning
confidence: 99%
“…The clinical trials, ClinicalTrials.gov NCT identifiers: NCT02208362, NCT01454596, NCT01109095, targeting IL-13Rα2, EGFRvIII, and HER2, respectively, provide useful insights on the immunotherapeutic ability of CAR T cells against gliomas (Migliorini et al, 2018). These trials showed the CAR T cells': low toxicity, moderate ability to traffic to the glioma microenvironment, limited ability to target glioma cells, and inconsistent results in increasing overall survival (Migliorini et al, 2018;Akhavan et al, 2019;Wang et al, 2020). For example, HER2-specific CAR T cells, in the NCT01109095 NCT00648739 Samalizumab Glioblastoma Recruiting Wright et al (2000), Gorczynski et al (2000), Wright et al (2003) trial, were used to treat 17 patients with progressive GBM (Ahmed et al, 2017).…”
Section: Car-t Cellsmentioning
confidence: 99%
“…ACTs using autologous TILs and CAR-T cells are the most prevalent strategy being explored in GBM, as evidenced by the number of completed or running clinical trials [ 272 ]. ACT by autologous lymphocytes relies on MHC-restricted tumor antigen recognition via T cell receptors (TCRs) [ 273 ]. It has also been demonstrated that TILs harvested from GBM patients can recognize and kill autologous tumor cells [ 274 ], but recent studies reveal that not all TILs are tumor-specific.…”
Section: Treatments In Developmentmentioning
confidence: 99%
“…CAR-T cells are engineered to directly recognize tumor-specific antigens (e.g., EGFR vIII , HER2, IL-13Rα2, EphA2.) in an MHC-independent manner [ 273 ]. As an example, single intravenous infusion of CAR-T cells redirected to EGFR vIII antigen in patients with recurrent GBM lead to the loss of EGFR vIII in 5/7 patients [ 278 ].…”
Section: Treatments In Developmentmentioning
confidence: 99%
“…The purpose of cell-based therapy is to enhance the anti-tumor activity of patient-derived T cells by engineering them to express either a chimeric antigen receptor (CAR) or a T cell receptor (TCR) targeting specific tumor antigens. However, this section will focus primarily on CAR-T cell therapy [ 58 ]. Unlike CAR-T cells, TCR-modified T cells rely on major histocompatibility class (MHC) peptide presentation, which GBM can suppress, thereby evading MHC-restricted T cell recognition and rendering TCR-modified T cells incapable of recognizing tumor-associated antigens (TAAs) [ 59 ].…”
Section: Recent Advances In Immunotherapymentioning
confidence: 99%